A Study of Various Medicinal Plants used in Ulcer Treatment: A Review - Awuchi, Chinaza Godswill; Saha, Purabi; Amle, Vandana Sonaji; Nyarko, Richard Owusu; Kumar, Roshan; Boateng, Edward Amoah; Kahwa, Ivan; Boateng, Paul Owusu; Asum, Christian (Journal for Research in Applied Sciences and Biotechnology, 2023)
Many people suffer from ulcer, a disorder of the digestive tract. Simply put, it's an inflamed break in the skin or the mucus membrane lining the digestive tract. Whenever there is a change in the equilibrium, such as increased aggression or decreased mucosal resistance, ulceration develops. Reasons for this could include drug use, poor diet, stress, and other similar factors. Peptic ulcers are a general term for any type of stomach or duodenal ulcer. To develop, peptic ulcers need mucosal defences to be compromised in addition to gastric juice acid and peptic activity. Ulcers can be treated with a variety of synthetic medications. However, compared to herbal remedies, these drugs are more costly and more likely to cause side effects. According to the research, many different ayurvedic doctors and traditional medicine practitioners use different medicinal plants and polyherbal formulations to treat ulcers. Peptic ulcer disease treatment should focus on symptom alleviation, ulcer healing, and preventing recurrence. In this article, we'll take a look at some medicinal plants that have been studied for their potential use in peptic ulcer treatment and prevention, both in ayurveda and Western medicine.